Traditional Ecological Knowledge in Environmental Assessment and Management - Usher, Peter J. (ARCTIC, 2000)
It is now a policy requirement that "traditional ecological knowledge" (TEK) be incorporated into environmental assessment and resource management in the North. However, there is little common understanding about what TEK is, and no guidance on how to implement the policy in public arenas where knowledge claims must be tested. The problems are inconsistent and unclear definitions of TEK, and insufficient attention to appropriate methods of organizing and presenting it for assessment and management purposes. TEK can be classified as knowledge about the environment, knowledge about the use of the environment, values about the environment, and the knowledge system itself. All categories are required for environmental assessment, but each must be presented and examined differently. TEK and "Western" science provide partially different information, based on different sets of observations and procedures, and sometimes on different knowledge claims. It is important that TEK be comprehensible and testable as a knowledge claim in public reviews, and usable for ongoing public monitoring and co-management processes. To this end, certain procedures are recommended for recording, organizing, and presenting TEK, with particular emphasis on the need to differentiate between observation and inference or association. Documenting TEK as recommended usually requires trained intermediaries, but they in turn require the support and cooperation of those who have TEK. One consequence is that it is often both impractical and inappropriate to require development proponents to incorporate TEK into their environmental impact statements. However, the environmental assessment process must facilitate the use of TEK in the public review phase. Les politiques publiques exigent maintenant que le «savoir écologique traditionnel» (SÉT) soit inclus dans les évaluations environnementales et la gestion des ressources du Nord. On ne s'accorde toutefois pas très bien sur la nature du SÉT et il n'existe pas de principes directeurs sur la façon ...